1996
DOI: 10.1002/chem.19960021020
|View full text |Cite
|
Sign up to set email alerts
|

Novel Heterocumulenes: Bisiminopropadienes and Linear Ketenimines

Abstract: Flash vacuum thermolysis (FVT) of suitably substituted isoxazol-5(4H)-ones 7-9 leads to three different types of ketenimines, namely, the isoxazolonoketenimines 2, the novel bisiminopropadienes RN=C=C=C=NR (9, and the C-cyanoketenimines 14, all characterized by a combination of FVT/matrix isolation/IR spectroscopy and FVT/MS. An unusual, linear C=C=N-C backbone in ketenimines 2g and 2h is revealed by their exceptional spectroscopic properties as well as an X-ray crystal structure of 2g. and confirmed by densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…1,2 Compound 2 has unusual properties for a ketenimine: a strong IR band at 2230 cm -1 (most ketenimines absorb at 2000-2090 cm -1 2,3 ) and 13 C resonances at 52 and 119 ppm that look more like those of a nitrile (37-77 and ca. 190 ppm are typical for the and R carbons of ketenimines, respectively 1,2 ). The X-ray structure of 2 revealed a short CdN bond (1.15 Å) and a linear CCNR moiety (∠CNR ) 179.6°).…”
Section: Introductionmentioning
confidence: 97%
“…1,2 Compound 2 has unusual properties for a ketenimine: a strong IR band at 2230 cm -1 (most ketenimines absorb at 2000-2090 cm -1 2,3 ) and 13 C resonances at 52 and 119 ppm that look more like those of a nitrile (37-77 and ca. 190 ppm are typical for the and R carbons of ketenimines, respectively 1,2 ). The X-ray structure of 2 revealed a short CdN bond (1.15 Å) and a linear CCNR moiety (∠CNR ) 179.6°).…”
Section: Introductionmentioning
confidence: 97%
“…Scheme 21 Bis(imino)propadienes 157 are reactive intermediates, obtainable by FVT of bis(aminomethylene)isoxazolones of the type 155. [112] Initial elimination of amine affords ketenimines 156, which are sometimes isolable. The compound 159 is particularly interesting because the X-ray structure, as well as the unusual 13 C NMR and IR data, revealed that the Ar group is collinear with the CϭCϭN moiety.…”
Section: Acetylenes Isocyanides and Cumulenes From Isoxazolonesmentioning
confidence: 99%
“…The compound 159 is particularly interesting because the X-ray structure, as well as the unusual 13 C NMR and IR data, revealed that the Ar group is collinear with the CϭCϭN moiety. [112] Further studies demonstrate that ketenimines with two electron-withdrawing substituents (X) at the carbon atom tend to have such collinear X 2 CϭCϭNϪR frameworks. [113] When either R or RЈ can be eliminated as an alkene in the bis(imines) 157, isomerization to cyanoketenimines 158 takes place.…”
Section: Acetylenes Isocyanides and Cumulenes From Isoxazolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…20 These compounds are generally highly unstable and can only be isolated at low temperatures. The diphenyl derivative 9 was obtained by FVT of the isoxazolone precursor 8 (Scheme 4) at 800…”
Section: Ph-n=c=c=c=n-phmentioning
confidence: 99%